The usage of nitrogen compounds by purple non-sulfur bacteria of the Rhodopseudomonas genus - О. V. Tarabas; S. О. Hnatush; О. М. Мoroz (Regulatory Mechanisms in Biosystems, 2019)
In this article, we characterized the regularities of oxidation of nitrite ions by phototropic purple non-sulfur bacteria Rhodopseudomonas yavorovii IMV B-7620, which were isolated from the water of Yavorivske Lake (Lviv Region, Ukraine). The bacteria were cultivated anaerobically at the light intensity of 200 lux and aerobically without illumination for 13 days in the modified ATCC No. 1449 medium. The concentration of nitrite ions was determined turbidimetrically by the turbidity of the solution by method of diazotization of sulfanilic acid by the nitrite ions and the interaction of the formed salt with n-(l-naphtyl)ethylenediamine dihydrochloride. The concentration of nitrate ions was determined turbidimetrically by the turbidity of the solution by method of diazotization. Zinc powder was used as a reducing agent. Efficiency of oxidation of 0.7–5.6 mM nitrite ions as electron donors by these bacteria was 100–7%, on the 10-th day of cultivation. It was established that nitrate ions were accumulated in the medium as a result of oxidation of nitrite ions by bacteria. The largest biomass (1.6 g/L) bacteria accumulated on the thirteenth day of growth in a medium with 2.8 mM NO2–. We found that R. yavorovii can use nitrate ions and urea as the only source of nitrogen for phototrophic growth. At a concentration of 1.9 mM ammonium chloride, sodium nitrite and urea in the cultivation medium, the biomass of bacteria was 1.2, 0.8, 1.0 g/L, respectively. The ability of the studied microorganisms to oxidize nitrite ions and to use nitrate ions indicates the significant impact of purple non-sulfur bacteria on the redistribution of streams of nitrogen compounds in ecosystems and the essential role of these microorganisms in the nitrogen biogeochemical cycle.